Prognostic value of multiparametric magnetic resonance imaging, transient elastography and blood‐based fibrosis markers in patients with chronic liver disease - Jayaswal, ANA; Levick, C; Selvaraj, EA; Dennis, A; Booth, JC; Collier, J; Cobbold, J; Tunnicliffe, EM; Kelly, M; Barnes, E; Neubauer, S; Banerjee, R; et al. (Wiley, 2020)
Background & Aims Liver cT1, liver T1, transient elastography (TE) and blood‐based biomarkers have independently been shown to predict clinical outcomes but have not been directly compared in a single cohort of patients. Our aim was to compare these tests’ prognostic value in a cohort of patients with compensated chronic liver disease. Methods Patients with unselected compensated liver disease aetiologies had baseline assessments and were followed up for development of clinical outcomes, blinded to the imaging results. The prognostic value of noninvasive liver tests at pre‐specified thresholds was assessed for a combined clinical endpoint comprising ascites, variceal bleeding, hepatic encephalopathy, hepatocellular carcinoma, liver transplantation and mortality. Results One hundred and ninety‐seven patients (61% male) with median age of 54 years were followed up for 693 patient‐years (median (IQR) 43 (26‐58) months). The main diagnoses were NAFLD (41%), viral hepatitis (VH, 25%) and alcohol‐related liver disease (ArLD; 14%). During follow‐up 14 new clinical events, and 11 deaths occurred.